Gonadotropins at Advanced Age - Perhaps They Are Not So Bad? Correlations Between Gonadotropins and Sarcopenia Indicators in Older Adults - Guligowska, Agnieszka; Chrzastek, Zuzanna; Pawlikowski, Marek; Pigłowska, Malgorzata; Pisarek, Hanna; Winczyk, Katarzyna; Kostka, Tomasz (Frontiers in Endocrinology, 2021)
Many hormones fluctuate during the aging process. It has been suggested that gonadotropins, which increase with age, contribute to the occurrence of many diseases and syndromes in older life, such as cardiovascular diseases, obesity, frailty syndrome and osteoporosis. This study aims to assess the relationship between circulating gonadotropins and other hormones potentially contributing to age-related functional decline and sarcopenia indicators in 39 male and 61 female community-dwelling seniors, mean age 80 years. According to the definition developed by the second European Working Group on Sarcopenia in Older People (EWGSOP2), the following indicators of the sarcopenia were assessed: bioimpedance-measured body composition, gait speed, handgrip strength, timed up and go test (TUG), chair stand test, Short Physical Performance Battery (SPPB). Blood levels of follicle-stimulating hormone (FSH), luteinizing hormone (LH), estradiol, testosterone, dehydroepiandrosterone sulphate (DHEAS) and cortisol were also measured. In the men, FSH and partially LH correlated positively with muscle mass percentage, gait speed, handgrip strength and SPPB, and negatively with percent body fat. Additionally, testosterone and DHEAS correlated negatively with the percentage of fat mass in men. Whereas in the women, FSH and LH were mainly negatively associated with body mass and adipose tissue measures. Cortisol did not show any relationship with the examined indicators. The study shows that the indicators of sarcopenia are strongly associated with levels of gonadotropins, sex hormones and DHEAS, especially in older men. The obtained results, after being confirmed in a larger group, may modify prevention and treatment strategies of sarcopenia.